(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
In the dynamic field of civil engineering, proficiency in computer-aided design (CAD) software is crucial. This study investigates the level of AutoCAD knowledge among civil engineering students in Edo State, Nigeria, and explores its implications for advancing contemporary civil engineering practices. The study assesses the extent to which civil engineering students in Edo State are familiar with AutoCAD. The research investigates whether students’ exposure to real-world applications impacts their AutoCAD skills. A mixed-methods approach was employed, combining surveys, interviews, and performance assessments. Participants included civil engineering students from universities and technical colleges in Edo State. The study anticipates varying levels of AutoCAD proficiency among students. The finding showed that civil engineering students in Edo State know AutoCAD and incorporate the software in their learning program. The result has implications for Contemporary Civil Engineering: The findings will inform educational institutions, policymakers, and industry stakeholders. In conclusion, bridging the AutoCAD knowledge gap among civil engineering students in Edo State holds immense potential for advancing the field and ensuring sustainable infrastructure development.